EFFECT OF DIFFERENT HYPERMEDIA PAGE LENGTHS ON LEARNING PERFORMANCE AND SATISFACTION - Eyuboglu, Filiz; Orhan, Feza (HACETTEPE UNIV, 2009)
This study investigated the learning performance and opinions of university students on hypermedia with different page lengths. The subjects were 127 undergraduate students from the Faculty of Education, YTU. Two hypermedia, one with long and the other with short pages, were designed by the researchers. The content presented on these hypermedia, the multiple choice test and a questionnaire to collect the opinions were also developed by the researchers. To analyze the findings independent group t-test and Mann-Whitney-U tests were utilized. Major finding of the study is that the page length did not affect the learning achievement of students. All students did well on both short and long page conditions, also they were all happy with the page length they worked on. This shows that designing computer-assisted or Web-based instructional materials with short pages as eveybody got used to is not a necessity for the university students.
Keywords: hypermedia; instructional material; learning; page length; long page; short page; COGNITIVE-STYLE; Education & Educational Research